Enhancing Drilling Parameters in Majnoon Oilfield - M. Majeed, Majid; A. Alhaleem, Ayad (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
The objective of drilling parameters optimization in Majnoon oilfield is to arrive for a methodology that considers the past drilling data for five directional wells at 35 degree of inclination as a baseline for new wells to be drilled. Also, to predicts drilling performance by selecting the applied drilling parameters generated the highest rate of penetration (ROP) at each section. The focal point of the optimization process is to reduce drilling time and associated cost per each well. The results of this study show that the maximum ROP could not be achieved without sufficient flow rate to cool and clean the bit in clay intervals (36" and 24") hole sections. Although the influence of combination of Weight on Bit (WOB), Round per minute (RPM), and hydraulic horsepower on the bit in (16", 12 1/4" and 8 1/2") hole sections is a key to reduce drilling time, therefore, the drilling parameters produced the fastest ROP per each section was considered as optimum parameters likely to apply for the future wells.